La stéréophonie législative, facteur de haute infidélité ? - Sparer, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
The object of this paper is to underline the inherent difficulty of expressing a single legislative intent in two languages. A number of basic issues concerning the translation of legal documents generally, and of statutes in particular, are formulated. These issues have been brought into sharp focus by divergent judicial interpretations of instruments drafted in French and referring to a civilian legal and cultural background. The practice of bilingual legislation is then considered. Reference is made to recent efforts at improving the French version of federal statutes. The need for, or usefulness of bilingual legislation is critically examined. Anglophone reactions to French unilingual legislation in Québec are explained in terms of adherence to the traditional English style of legislative drafting. However, it is pointed out that common lawyers may be looking with increasing interest at the attributes of clarity, simplicity and logic associated with the civilian style of drafting.